This pen for hire ebook - Levine, Laura (Jaine Austen Mystery., 2009)
"I'm crazy about Laura Levine's mystery series. Her books are so outrageously funny." —Joanne Fluke Smarmy personals ads. Daring declarations of love. Freelance writer Jaine Austen has penned them all. But no one needs her help more than geeky, gawky Howard Murdoch. His request is simple enough: a letter proclaiming his undying love for Stacy Lawrence, a gorgeous aerobics instructor. The fact that he's never actually met the woman gives Jaine pause—yet she soon overcomes her misgivings, and the unlikely Romeo lands a date! But his triumph is short-lived. On Valentine's Day, Howard finds Stacy bludgeoned to death with a Thigh Master—and is quickly named the prime suspect. Jaine is shocked. Sure, Howard's awkward and eccentric. But a murderer? That's hard to believe. Especially after a little sleuthing reveals a plethora of people who harbored less-than-loving feelings towards the svelte Stacy. Now Jaine had better wrangle her clues quickly, before a crafty killer catches on—and puts a whole new spin on her ghost writing career. . . "Sheer fun!" —Carolyn Hart